Reimagining Human Presence in AI Mediated Learning Environments - Aliah Bagus Purwakania Hasan (Education Achievement: Journal of Science and Research, 2026)
The integration of artificial intelligence (AI) in the world of education is growing rapidly and bringing significant changes to the learning process. While AI technology offers personalized learning, automation, and adaptive feedback, its existence also raises questions about the role and meaning of human presence in AI-mediated learning environments. This study aims to reconstruct the concept of human presence in an AI-based learning environment and analyze its reinforcement strategies to support learning effectiveness. This study uses a descriptive qualitative approach through literature studies and reflective analysis of AI-based learning practices in higher education. Data were obtained from scientific articles, education policy documents, and practices of implementing AI in the context of learning. The analysis focused on the three dimensions of human presence, namely cognitive presence, social presence, and instructional presence. The results show that AI-mediated learning environments do not eliminate human presence, but rather transform them. Human presence continues to play an important role in guiding critical thinking processes, building social interactions, and ensuring that learning takes place in a contextual and ethical manner. However, without a planned pedagogical design, the use of AI has the potential to reduce the relational and affective dimensions of learning. Therefore, AI integration needs to be based on a human-centered approach that places educators as reflective facilitators and guardians of human values in the educational process. This study concludes that the reimagination of human presence in an AI-based learning environment demands a balanced synergy between technological innovation and pedagogical intentionality, so that AI functions as a supporting tool, not a substitute for the role of educators.